A broader evaluation of vaccine-induced T cell immunity against tuberculosis - Ogongo, Paul (Frontiers in Tuberculosis, 2024)
Although Bacillus Calmette-Guérin (BCG) vaccine, the only licensed vaccine against tuberculosis (TB), is the most widely used vaccine worldwide, TB is the second leading global killer from a single infectious agent responsible for over one million deaths annually. With the increasing threat of the emergence of drug-resistant TB, there is intense research toward better and more efficacious vaccines against TB. Indeed, TB vaccine research has blossomed in recent years: demonstration of sterilizing immunity against Mycobacterium tuberculosis (Mtb) challenge in non-human primates, the potential benefit of BCG revaccination in humans, and a phase IIb vaccine with ~50% efficacy against developing active disease. Consequently, several vaccines are set to begin phase 3 trials in 2024, and new candidates have entered phase 1 including mRNA-based TB vaccines. However, despite the enthusiasm, there are no known correlates of protection against TB, the antigens that induce protective immunity are incompletely defined, and the overreliance on Th1 cytokine production as an 'absolute' measure of protection is increasingly debatable. In this perspective, I highlight the recent milestones in TB Vaccine research and the remaining challenges and propose suggestions for future considerations.